Produção de biossurfactantes por fermentação submersa utilizando extrato aquoso da algaroba [Prosopis juliflora (Sw) DC] como substrato - Dias, Emanuele Cardoso (2017)
Biosurfactants are amphipathic molecules synthesized by microorganisms that act at the water/oil or oil/water interfaces, reducing the surface and interfacial tensions between them and thus making some compounds more miscible. In comparison to the synthetic surfactants that are on the market, they present several advantages, such as biodegradability and low toxicity giving them important importance. The use of non- conventional substrates, mainly renewable, is a strategy of biosurfactants production due to the low cost offered, constituting one of the most important factors for the economic feasibility on an industrial scale. In this work, the production of biosurfactants by Bacillus subtilis using the aqueous extract of the algaroba as alternative substrate was studied, using a 2² factorial experimental design with triplicate in the central point, to evaluate the influence of the concentration of this substrate and yeast extract in this production. In view of the results, the increase of the concentration of the algaroba aqueous extract with yeast extract supplementation favored the growth of the microorganism and the production of biosurfactants, as evidenced by the factorial design. The indicative of biosurfactant production, emulsification index, was higher in the culture using the supplementation at 0.5 and 1.0 % of yeast extract. According to the emulsification index, levels equivalent to those found in the literature were reached, and also highlighting the product from bioreactor test that showed an efficacy proportional to the synthetic surfactant SDS. Finally, considering the similarity shown in the spectrograms with IRs found in the industrial surfactin, it is also concluded that the biosurfactant found in this submerged fermentation process corresponds to lipopeptides. The results indicate the feasibility of producing biosurfactants from the aqueous extract of the algaroba, a low cost and abundant substrate in the Northeast region.